Robin Watkins' 5th Birthday Party at Home - Watkins, Howard::::::::: (1987)
Christine Watkins cutting birthday cake; Frances Kamp and Laurie Tidyman-Jones in background Party under backyard patio; Dustin Tidyman-Jones sitting at little children's table